In-built fabrication of MOF assimilated B/N co-doped 3D porous carbon nanofiber network as a binder-free electrode for supercapacitors. (1st April 2019) - Dahal, Bipeen; Mukhiya, Tanka; Ojha, Gunendra Prasad; Muthurasu, Alagan; Chae, Su-Hyeong; Kim, Taewoo; Kang, Dawon; Kim, Hak Yong
Abstract: Polyacrylonitrile (PAN) based carbon nanofibers (CNFs) show enormous potential as a high performance and cost-effective supercapacitor electrode material. However, there are two intrinsic limitations that prevent their deployment in this field, namely their low surface area and limited transporting channels for ion diffusion. Here, we design an approach that concurrently addresses both problems. We employ electrospinning of PAN and zeolitic imidazolate framework (ZIF-8) nanoparticles to fabricate highly porous CNFs, followed by a sodium borohydride treatment and freeze-drying to maintain the three-dimensionalities of carbon nanofibers networks. Nitrogen and boron co-doping could be achieved together by controlling the conditions for stabilization and carbonization after the ammonium borate tri-hydrate treatment. The novel ZIF-8 incorporated 3D nitrogen and boron co-doped carbon nanofiber electrode was tested as a binder-free supercapacitor electrode and delivered a high specific capacitance of 295 F g −1 at a 0.5 A g −1 current density, exceeding that of PAN-based carbon nanofiber supercapacitor electrodes. Indeed, the novel electrode also maintained a high rate capability and remarkable cyclic stability of 94.5% capacitance retention even after 10 000 charge-discharge cycles. This superior electrochemical performance is attributed to the large surface area, mesoporous nature and high wettability of the B and N doped carbon nanofiber electrode. This study will inspire the development of new 3D PAN and metal organic framework based porous electrode materials for high performance energy storage devices. Graphical abstract: Image 1